2013 IEEE Third International Conference on Consumer Electronics ¿ Berlin (ICCE-Berlin) 2013
DOI: 10.1109/icce-berlin.2013.6698051
|View full text |Cite
|
Sign up to set email alerts
|

HEVC performance and complexity for 4K video

Abstract: Abstract-The recently finalized High-Efficiency Video Coding (HEVC) standard was jointly developed by the ITU-T Video Coding Experts Group (VCEG) and the ISO/IEC Moving Picture Experts Group (MPEG) to improve the compression performance of current video coding standards by 50%. Especially when it comes to transmit high resolution video like 4K over the internet or in broadcast, the 50% bitrate reduction is essential. This paper shows that real-time decoding of 4K video with a framelevel parallel decoding appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…11,12 In addition, studies regarding the HEVC software decoding performance and complexity for high resolution sequences have been also performed. 13 As already noted in the introduction, the inter-picture prediction in HEVC relies on MVs with quarter sample accuracy similarly to the inter-picture prediction in H.264/MPEG-4 AVC. However, for the MVP derivation, the median based predictor using spatially neighboring MVs was replaced by a competitive scheme, which is applied on a set of candidates derived from both spatial and temporal neighboring MVs.…”
Section: Background and Related Workmentioning
confidence: 94%
“…11,12 In addition, studies regarding the HEVC software decoding performance and complexity for high resolution sequences have been also performed. 13 As already noted in the introduction, the inter-picture prediction in HEVC relies on MVs with quarter sample accuracy similarly to the inter-picture prediction in H.264/MPEG-4 AVC. However, for the MVP derivation, the median based predictor using spatially neighboring MVs was replaced by a competitive scheme, which is applied on a set of candidates derived from both spatial and temporal neighboring MVs.…”
Section: Background and Related Workmentioning
confidence: 94%
“…It has been demonstrated that by using SIMD and multithreading it is possible to achieve very high performance for HEVC decoding on recent computer architectures [Bossen et al 2012;Chi et al 2014;Bross et al 2013]. As a result, much higher than real-time frame rates can be achieved even for UHD resolution videos on commodity desktop and mobile processors.…”
Section: Introductionmentioning
confidence: 99%
“…[15] shows that real-time decoding of 4K video with a frame-level parallel decoding approach using four desktop CPU cores is feasible.…”
Section: H265 Video Codecmentioning
confidence: 99%